Emotions, memory and reading comprehension among high school student - Scandar, Mariano (2020)
Background: the existence of specific effects of emotion on text comprehension in adults has been experimentally verified. However, there is no information regarding adolescents, which is relevant for the design of interventions. Objective: this research study aims to assess whether dimensionallyconceptualized emotional states (valence, arousal and dominance) affect the comprehension and retrieval of written texts in adolescents. Method: following instrument validation, three experiments (n = 468) were performed. They consisted in inducing emotions which differed in one dimension (valence, arousal or dominance) and kept others the same, in order to assess the role of each dimension on comprehension and retrieval processes (i.e., positive vs. negative valence; stable arousal and dominance in experiment 1). Results: the results indicate that valence has an impact on text comprehension and shows a better performance in positive than negative emotional states. On the other hand, activation occupies a central role in memory processes independently of other emotional dimensions, with higher performance in high activation states. Finally, dominance did not show any significant effect. Conclusions: the results suggest that the valence of emotional states is mostly related to reasoning and induction processes, while activation is associated with changes in information storage and retrieval processes. Contribution of authorship MS: design and design of the studio, administration of techniques, interpretation of them data and final review of the manuscript. NI: supervision of the research design, statistical advice, discussion and final review of the manuscript.